PENGARUH KUALITAS PELAYANAN DAN CITRA PERUSAHAAN TERHADAP LOYALITAS KONSUMEN PADA HOTEL GRAND SUKA PEKANBARU - Yenni Haryani; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research was conducted at the Grand Suka Hotel Pekanbaru located on Jl. Soekarno Hatta Kav.148 Pekanbaru, Riau. The purpose of this study was to determine the effect of service quality and corporate image on consumer loyalty in the case of Grand Suka Hotel Pekanbaru partially and simultaneously. In this research, the method used is descriptive quantitative analysis with SPSS program. The population in this study were all consumers who purchased rooms at the Grand Suka Hotel Pekanbaru in the last year, 2020 as many as 23,356 and the sample from this study was 100 respondents. To determine the sample using the Slovin formula, namely the non-probability sampling technique with the accidental sampling technique. Data collection techniques through questionnaires and interviews, types and sources of data using primary data and secondary data, measurement collection techniques using a Likert scale. From data analysis which includes validity test, reliability test, simple linear regression analysis, multiple linear analysis, determination analysis and significance test with t test test (partial test), and f test (simultaneous test). The results of this study indicate that the results of testing the first t test hypothesis, Service Quality on Consumer Loyalty, namely t count (6.044) > t table (1.6605) meaning that Service Quality has a significant effect on Consumer Loyalty. Second, Company Image on Consumer Loyalty, namely t count (6,296) > t table (1,6605) meaning that Company Image has a significant effect on Consumer Loyalty. The results of the f test of Service Quality and Corporate Image have a significant effect on Consumer Loyalty, namely f count (25.116) > F_table (3.09). This means that the Quality of Service and Company Image simultaneously have a significant effect on Consumer Loyalty at Grand Suka Hotel Pekanbaru. Keywords: Service Quality, Corporate Image, Consumer Loyalty